2019
DOI: 10.2147/jmdh.s211420
|View full text |Cite
|
Sign up to set email alerts
|

<p>Self-medication practices among Vietnamese residents in highland provinces</p>

Abstract: Background: Monitoring self-medication practice, which refers to individuals using medicine without instructions of physicians, is critical to control its harmful effects. However, in Vietnam, evidence about self-medication among individuals in highland areas is constrained. This study examined self-medication practice among residents living in highland areas in Vietnam and determined associated factors. Materials and methods: A cross-sectional study was performed in five hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 31 publications
(42 reference statements)
3
18
2
2
Order By: Relevance
“…We presume the underlying cause of this phenomenon is that in our sample, the majority of farmers merely went to visit and to achieve health information from medical professionals once they had severe health problems. Indeed, our hypothesis was supported by previous studies that showed approximately 50%–80% of inhabitants in rural and mountainous sites of Vietnam habitually practised self-treatment or self-medication 34–36 or visited nearby traditional healers. 37 38 Additionally, our regression model indicated that multiple concurrent diseases were statistically linked to psychological distress.…”
Section: Discussionsupporting
confidence: 83%
“…We presume the underlying cause of this phenomenon is that in our sample, the majority of farmers merely went to visit and to achieve health information from medical professionals once they had severe health problems. Indeed, our hypothesis was supported by previous studies that showed approximately 50%–80% of inhabitants in rural and mountainous sites of Vietnam habitually practised self-treatment or self-medication 34–36 or visited nearby traditional healers. 37 38 Additionally, our regression model indicated that multiple concurrent diseases were statistically linked to psychological distress.…”
Section: Discussionsupporting
confidence: 83%
“…In this study, we found that 33.7% of people self-treated during the past three months. This result was lower than in some studies in the world and Vietnam [ 5 , 23 , 37 40 ]. This difference is probably due to the different recall times, as previous studies often asked for 12 months, while our study asked for three months because we want to limit recall bias which occur when people have to remember events for long periods.…”
Section: Discussioncontrasting
confidence: 67%
“…A study from 1998 found that the rate of self-treatment in mountainous areas was 57% in the last four weeks [ 23 ]. Another recent study showed that 83.3% of people in mountainous areas in Central Vietnam had self-treatment practices in the last 12 months [ 5 ]. Self-treatment is mainly based on personal experience or advice from friends, relatives, and drug sellers.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, community pharmacists continue to play a key role in managing diseases in Vietnam with for instance over 80% of people typically visiting a pharmacist first for their illness. These scenarios are common especially in rural areas to conserve costs for patients and enhance profits for pharmacists; however, rates of selfpurchasing of medicines are lower than before enhanced by increased social insurance (113,(123)(124)(125). Despite this, the costs of medicines can still be a concern in Vietnam with high costs vs. IRP (126).…”
Section: General and Asiamentioning
confidence: 99%